Reactivity Effects in a Very-High-Temperature Pebble-Bed Reactor - D. M. Pérez; L. H. Pardo; D. M. Pérez; L. P. R. Garcia; D. E. M. Lorenzo; C. A. B. de Oliveira Lira (Atom Indonesia, 2021)
The very-high-temperature reactor (VHTR) is one of the most promising and innovative designs selected by the Generation IV International Forum. Although previous papers have focused on the study and optimization of several parameter of a VHTR conceptual design, there is still much work needed to achieve the commercial introduction of this technology. The primary aim of this study is to obtain the reactivity effects of such parameters as the temperature of the fuel, moderator, and reflector, and the poisoning by 135Xe and 149Sm in the VHTR critically. To reach this goal, the widely-used MCNP6 code was employed in order to simulate the neutronics of the VHTR. The viability of the utilization of the MCNP6 code and the developed model for the study of the physics of the VHTR core was confirmed through the calculation and comparison with benchmarks provided by the IAEA. Based on the results of the temperature coefficients of reactivity obtained, a negative reactivity effect on the system of about 12 pcm/K was found, as is expected in all the nuclear fission reactors, while the combined effect of fission products 135Xe and 149Sm implies a negative reactivity of 3475 pcm.